Transformational and Transactional Leadership Improve Performance: Evidence From Lecture Faculty of Economics University of Ichsan Gorontalo - Juriko Abdussamad; Ariawan Ariawan (AIBPM Publisher, 2018)
The success of a leader in improving the performance of its members is very dependent on his behavior in carrying out leadership functions in his leadership strategy. Faculty leaders in universities need to apply transformational and transactional leadership so that the performance of the lecturer is able to achieve the desired goals. This study aims to determine the effect of transformational and transactional leadership on the performance of the lecturers of the economics faculty of University of Ichsan Gorontalo with a sample of 31 active teaching lecturers, using a quantitative approach with SEM-PLS analysis using the WarpPLS program. The results of the study showed that the effect of transactional leadership had a positive and significant effect on the performance of lecturers, which had a greater influence than the influence of transformational leadership on the performance of lecturers. Keywords: leadership, transformational, transactional, lecturer performance.